Create better lessons quicker
Correto: (√5 – 2).(√5 + 2) = 1, (x+a)² = x² + 2ax+ a², (x-a)² = x² - 2ax+ a², (x+a)(x-a) = x² - a², (x+2)² = x² + 4x + 4, ( x- 3 )² = x² - 6x + 9, ( x+ 4 )( x- 4 ) = x² - 16, (3x – 4z)² = 9x² – 24xz + 16z², (2 + x)³ = x³ + 6x² + 12x + 8, (2 – x)³ =  – x³ + 6x² – 12x + 8, Incorreto: (√5 – 2).(√5 + 2) = 2√5, (x+a)² = 2x+ 2a, (x+a)² = 2x - 2a, (x+a)(x-a) = 2x, (x+2)² = 2x + 4, ( x- 3 )² =2 x- 6, ( x+ 4 )( x- 4 ) = 2x, (3x – 4z)² = 6x – 8z , (2 + x)³ = 6 +3x , (2 – x)³ = 6 – 3x,

Acertando os Produtos Notáveis

Switch template

Interactives

Leaderboard

Similar activities from Community

Switch template

Interactives